FACTORS INFLUENCING FIRM VALUE WITH FIRM SIZE AS MODERATING VARIABLE - Denny , Denny; Yanti, Yanti (International Journal of Application on Economics and Business, 2025)
This study aims to analyze the influence of capital structure and asset management on the firm value of property and real estate companies listed on the Indonesia Stock Exchange, with firm size as a moderating variable. The research utilizes purposive sampling, resulting in data from 35 companies during the 2020-2022. Data analysis was conducted using multiple regression analysis with the assistance of Eviews software version 13. The findings indicate that capital structure has a significant positive effect on firm value, while asset management has no significant effect on firm value. Furthermore, firm size weakens the relationship between capital structure on firm value while firm size does not influence the relationship between asset management on firm value.